ANALISIS RELOKASI PEMBANGKIT LISTRIK TENAGA SURYA ON-GRID KAPASITAS 75 kWp DI SMKN 1 DENPASAR - Agus, M.N.; Gunawan, J.N.; Amrita, A. A. N.; Hartati, R. S. (Jurnal SPEKTRUM, 2024)
The solar energy potential in Bali ranges from 4.01 to 6.13 kWh/m²/day, with an average increase of 4.89 kWh/m²/day. For solutions and innovations in energy development from unlimited resources, the use of new renewable energy such as natural sources like the sun is being explored. The utilization of renewable energy sources in the production of electricity and the decision of the Minister of Energy and Mineral Resources, Ministerial Regulation ESDM No. 49 of 2018, concerns the use of rooftop solar energy systems by consumers of PT PL).. The presence of the PLTS Rooftop at SMKN 1 Denpasar has garnered attention for further analysis regarding the installed PLTS. The performance of the PLTS Rooftop system at SMKN 1 Denpasar is analyzed using PVSyst software to view production potential, then calculate performance parameters of the PLTS system compared to the production results during one year of operation. The relocation design of the rooftop PLTS was carried out using PVSyst software, and then the performance parameters in the new building were calculated. Based on the analysis, the rooftop PLTS at the building before relocation produced an energy output of 124,347 kWh/Year with a performance ratio of 85.6%. For the building after relocation at SMKN 1 Denpasar, the energy output of the PLTS is 133,977 kWh/Year with a performance ratio of 85.7%.